Yield enhancement and nutrient uptake through soil amelioration and foliar nutrition in rice (Oryza sativa L.) in Vaikom Kari soils: Yield enhancement and nutrient uptake in rice - S, Sreelekshmi; Devi, VS (ORYZA-An International Journal of Rice, 2025)
A field experiment was carried out in Vaikom kari soils of Kuttanad, during puncha season from October 2020 to February 2021 with an objective to augment the yield and nutrient uptake of rice in Vaikom kari soils through soil amelioration practices for managing soil acidity, and by supplementing nutrition at panicle initiation stage through foliar application of potassium and micronutrients. The experiment was laid out in Factorial Randomized Block Design with two factors in which factor A consisted of three levels of dolomite application in soil : No dolomite application (D0), Ordinary dolomite application basally and at 30 DAS (D1) and granulated dolomite application basally and at 30 DAS (D2), and factor B consisted of five levels of foliar nutrition: without foliar application (N0), foliar spray  of 1% KNO3  (N1), foliar spray  of 1% K2SiO3  (N2), foliar spray  of 1% KNO3 + 0.5% micronutrient solution (N3) and  foliar spray of 1% K2SiO3 + 0.5% micronutrient solution (N4)  at panicle initiation (PI) stage. Analysis of experimental results indicated that the treatments had significant effect on yield and yield attributes and uptake of nutrients in grain and straw as compared to control. The result revealed that application of granulated dolomite as basal and at 30 Days after sowing along with foliar nutrition of 1% KNO3 or combined spray of 1% KNO3 with 0.5% micronutrients at PI stage were found to be more effective in enhancing grain yield and nutrient uptake of rice in Vaikom kari soils.